STRENGTHENING RELIGIOUS MODERATION BASED ON THE TUROTS FOR MIGRANT WORKERS IN BUSAN SOUTH KOREA - Ahmad Khoirul Mustamir; Reza Ahmad Zahid; Syaikhoni (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
The focus of this community service is on the religious awareness of Muslim migrant workers in Busan, South Korea, regarding religious moderation. Since the Indonesian government launched the idea of religious moderation, there has been no program to address Muslim migrant workers abroad. In fact, the existing phenomenon is the potential for religious non-moderation awareness. They come into contact with preachers from countries outside Indonesia. In this context, this Community Service Program (PKM) is conducted using participatory action research (PAR). The first steps taken are identifying problems, conducting preparations through in-depth discussions, conducting activities, and conducting evaluations. The moderation literacy used values ​​of moderation sourced from classical books (turots) in the book of national fiqh. This success is supported by an implementation strategy that involves infiltrating the values ​​of religious moderation using classical books (turots) compiled in the book of national fiqh. The greatest success of this activity is the awareness of Muslim migrant workers about the importance of religion as a nurturing, balancing values ​​in religious, national, and state life.